The role of stress and immune system in psychiatric disorders - Leonard, Brian (Henry Stewart Talks, 2007)
The relationship between neurotransmitters and the HPA axis, The role of stress in psychiatric disorders, Effects of stress or depression on the HPA axis and the immune system, The role of the immune system in psychiatric disorders, Basic aspects of psychoimmunology